A Study Of Bacteriological Profile In Urine Sample Of Pregnant Patients Diagnosed As Threatened Preterm Labour (International Journal of Food and Nutritional Sciences, 2022)
Background: Preterm laboris a challenging issue contributing to perinatal morbidity and mortality all over the world. Preterm labour has multifactorial ethology, but it has been found that 40% of all cases of spontaneous preterm labour and preterm birth are linked to infections, the most common being Bacterial Vaginosis.Aim and Objective: The present study was aimed to study bacteriological profile in urine sample of pregnant patients diagnosed as threatened preterm labourMethodology: This case control observational study was conducted at Santosh Medical College and Hospital, Ghaziabad, between the periods of 19th April 2019 and 30th september2020. There were 120 pregnant women recruited out of which 60 women with threatened preterm delivery were considered in the case group, whereas; the remaining 60 antenatal women that had crossed 37 weeks, but less than 40 weeks of gestation, and had no pregnancy complication during the course of the present pregnancy were included in the control group. Data collection was done by screening the pregnant women based on the patient history, examination and laboratory findings.Result: In control group and case group, majority of patients were between the age of 25 to 29 years, that is 51.7% and 48.3% respectively. 21.66% patients in control group were primigravida and 78.33% were multigravida, where as in the case group 18.3% were primigravida and 81.7% were multigravida. Urine culture in control group was sterile in 96.66% of the patients and 3.33% had E. coli, where as in case group 26.66% had E. coli.Conclusion: Pregnant women must be screened and treated for urogenital infections at their first antenatal appointment in order to reduce the risk of premature labor, preterm birth, and the associated maternal and fetal morbidities.